Copper-Catalyzed Regioselective Direct C–H Thiolation and Thiocyanation of Uracils - Medena Noikham (2020)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim A novel copper-catalyzed direct C–H thiolation and thiocyanation of uracils using disulfides and thiocyanate salts respectively as coupling partners are described. These reactions enable the C–H bond cleavage and C–S bond formation to proceed efficiently under relatively mild conditions, providing useful methods for a preparation of a series of thio-substituted at the C5 position of uracil derivatives. These protocols exhibit several merits including simple experimental procedures, readily accessible substrates and reagents, broad scopes, high yields, and excellent regioselectivity. Preliminary mechanistic studies revealed that a radical pathway is likely to be involved.